Pemakaian Pupuk Organik Cair Sebagai Dekomposer dan Sumber Hara Tanaman Padi (Oriza sativa L.) - Isnawan, Bambang Heri; Utama, Nafi Ananda (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2015)
A research to determine the effects of liquid organic fertilizer as a decomposer and nutrition source on the growth of rice plant (Oriza sativa L.). This research was conducted in Wirokerten, Botokenceng, Bantul, Yogyakarta. Field experiment was Â arranged using Randomized Completely Block Design with 2 factors and three replications. The first factor was liquid organic fertilizer, consist of liquid organic fertilizer and witout liquid organic fertilizer. The second factor was the doses of SRI, consist of 25% SRI, 50% SRI, 75% SRI and 100% SRI (urea fertilizer 350 kg/ha, 150 kg/ha of SP-36 fertilizer and 150 kg/ha of KCl fertilizer). The result showed that the liquid organic fertilizer with dose 10 l/ha macro fertilizer and 5 l/ha micro fertilizer were not significantly increased the growth and yield of rice plant. Liquid organic fertilizer with dose 75% SRI was significantly increased the leaf number than dose of 25% and 100% SRI. Doses 25% and 100% of SRI with application the liquid organic fertilizer was significantly increased the weight of 1000 seeds. Doses of SRI was not significantly increased the rice yield per hectar.